2020
DOI: 10.3390/cells9030647
|View full text |Cite
|
Sign up to set email alerts
|

ABCA1/ABCB1 Ratio Determines Chemo- and Immune-Sensitivity in Human Osteosarcoma

Abstract: The ATP Binding Cassette transporter B1 (ABCB1) induces chemoresistance in osteosarcoma, because it effluxes doxorubicin, reducing the intracellular accumulation, toxicity, and immunogenic cell death induced by the drug. The ATP Binding Cassette transporter A1 (ABCA1) effluxes isopentenyl pyrophosphate (IPP), a strong activator of anti-tumor Vγ9Vδ2 T-cells. Recruiting this population may represent an alternative strategy to rescue doxorubicin efficacy in ABCB1-expressing osteosarcoma. In this work, we analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 57 publications
2
41
0
1
Order By: Relevance
“…3D tumour models are considered to better recapitulate the in vivo tumour microenvironment compared to standard 2D cultures. In this review we have identified a total of 37 publications [ 34 , 50 , 57 , 60 , 62 , 64 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ] where 3D culture significantly altered cancer cell behaviour towards a more biomimetic response. Eighteen of these studies used 3D scaffold-based cultures and 18 studies used non scaffold-based, cell-generated extra-cellular matrix (ECM) cultures, with a single study using both approaches [ 73 ] ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…3D tumour models are considered to better recapitulate the in vivo tumour microenvironment compared to standard 2D cultures. In this review we have identified a total of 37 publications [ 34 , 50 , 57 , 60 , 62 , 64 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ] where 3D culture significantly altered cancer cell behaviour towards a more biomimetic response. Eighteen of these studies used 3D scaffold-based cultures and 18 studies used non scaffold-based, cell-generated extra-cellular matrix (ECM) cultures, with a single study using both approaches [ 73 ] ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…3D SaOS2 and U2OS cell spheroids were also generated by using commercial culture plates coated with various matrix: hyaluronic acid, collagen and adhesion proteins (Biomimesys™ matrix, from HCS Pharma, France). By using such an approach, 3D cultures differentially modulated the ATP binding cassette transporter A1 (ABCA1) and B1 (ABCB1, also known as Multidrug resistance protein-1, MDR1) expressions associated with the drug efflux and resistance which has not been observed in 2D environments [70] . 3D culture cells exposed to doxorubicin were characterised by a higher expression of ABCB1 implicated in the intracellular drug efflux, induced by the ERK1/2/HIF-1 pathway.…”
Section: D Culture Methods Of Primary Bone Tumoursmentioning
confidence: 99%
“…Fanelli et al used a small molecular inhibitor CBT-1 to prevent ABCB1- and ABCC1-mediated efflux, reversing doxorubicin resistance in vitro [ 9 ]. Belsario et al proposed that an increased ratio of ABCB1/ABCA1 indicates higher doxorubicin resistance [ 10 ]. ABCA1 effluxes isopentenyl pyrophosphate, which is known to recruit anti-tumor T-cells, providing a novel immune-stimulatory mechanism to potentially treat osteosarcoma.…”
Section: Altered Drug Transportmentioning
confidence: 99%
“…Their study found that tumors high in ABCB1 expression were often low in ABCA1 expression, thus having simultaneous doxorubicin and T-cell resistance. They were able to reverse this phenotype with nanoparticle-encapsulated zoledronic acid, highlighting a potential mechanism to overcome resistance to doxorubicin and immune escape [ 10 ].…”
Section: Altered Drug Transportmentioning
confidence: 99%